Towards Chinese Learner's Dictionaries for Foreigners Living in China: Some Problems Related to Lemma Selection - Xue, Mei; Tarp, Sven (Lexikos, 2018)
During the past decades, various dictionaries for foreign learners of Chinese have seen the light. Except for one picture dictionary which is almost completely ignored in the academic literature, none of these dictionaries has taken into account the special needs which foreigners living in China and learning Chinese may have. This contribution will discuss these needs with special focus on lemma selection. We argue that foreigners living in China, in order to meet their lexicographical needs, require additional words typically occurring in social contexts in which they often find themselves, whether or not these words have a high corpus-frequency. As a solution we therefore recommend a set of selection criteria that combines corpus frequency and context relevance. Finally, we discuss how logfiles reflecting user behaviour can be used as a new and very reliable empirical source for lemma selection for an online Chinese learner's dictionary.